2019
DOI: 10.1002/cam4.2153
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy plus dasatinib leads to comparable overall survival and relapse‐free survival rates as allogeneic hematopoietic stem cell transplantation in Philadelphia positive acute lymphoblastic leukemia

Abstract: Background The Philadelphia chromosome is associated with a poor prognosis in acute lymphoblastic leukemia (ALL). While hematopoietic stem cell transplantation (HSCT) has been regarded as a favorable treatment option in adult Philadelphia‐positive (Ph+) ALL, its benefit is less clear in the era of newer generation tyrosine kinase inhibitors (TKIs) like dasatinib. Methods This was a retrospective study that analyzed the outcomes of adult patients with Ph+ ALL treated with either combination chemotherapy plus da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…I 2 = 73%) [11,16,26,30,33,36,37] (S4A and S4B Fig) . In addition, the pooled result between allo-HSCT group and auto-HSCT group were not significantly different (pooled OR of OS 0.93; 95% CI, 0.54-1.60; I 2 = 0%) [14,25] (S4C Fig).…”
Section: Plos Onementioning
confidence: 96%
See 4 more Smart Citations
“…I 2 = 73%) [11,16,26,30,33,36,37] (S4A and S4B Fig) . In addition, the pooled result between allo-HSCT group and auto-HSCT group were not significantly different (pooled OR of OS 0.93; 95% CI, 0.54-1.60; I 2 = 0%) [14,25] (S4C Fig).…”
Section: Plos Onementioning
confidence: 96%
“…Subgroup analysis of studies with all Ph + ALL patients achieving CR1 prior to allo-HSCT or CMT showed increased pooled OR of OS to 1.75 (95% CI, 1.00-3.06; I 2 = 64%) [10,11,16,24,26,30,33,34,36,37] while pooled OR of DFS was decreased to 2.69 (95% CI, 1.27-5.72;…”
Section: Subgroup Analysis Of Studies With All Ph + All Patients Achieving Cr1 Before Hsct/cmtmentioning
confidence: 99%
See 3 more Smart Citations